Precisão de diferentes pontos de corte do índice de massa corporal para identificar sobrepeso de acordo com valores de gordura corporal estimados por DEXA - Anzolin, Caroline Cristina [UNESP]; Silva, Diego Augusto Santos; Zanuto, Edner Fernando [UNESP]; Cayres, Suziane Ungari; Codogno, Jamile Sanches [UNESP]; Costa Junior, Paulo [UNESP]; Machado, Dalmo Roberto Lopes; Christofaro, Diego Giulliano Destro [UNESP] (Elsevier, 2017)
Objective To evaluate the sensitivity and specificity of different cutoff points of body mass index for predicting overweight/obesity according to body fat values estimated by DEXA among Brazilian adolescents. Methods Cross-sectional study including 229 male adolescents aged 10–15 years, in which body adiposity and anthropometric measures were assessed. Nutritional status was classified by BMI according to cutoff points described in scientific literature. Results Moderate agreements were observed between body fat estimated by DEXA and cutoffs proposed by Cole et al. (K = 0.61), Conde and Monteiro (K = 0.65), Must et al. (K = 0.61) and WHO (K = 0.63). The BMI in continuous form showed good agreement with the Dexa (ICC = 0.72). The highest sensitivity was observed for cutoff by Conde and Monteiro (0.74 [0.62, 0.84]) and the highest specificity by Cole et al. (0.98 [0.94, 0.99]). For the areas under the ROC curve of cutoff points analyzed, significant difference comparing the cutoff points by Cole et al. and Conde and Monteiro (0.0449 [0.00294, 0.0927]) was observed. Conclusions The cutoff proposed by Conde and Monteiro was more sensitive in identifying overweight and obesity when compared to the reference method, and the cutoff proposed by Cole et al. presented the highest specificity for such outcomes.
Accuracy of different cutoff points of body mass index to identify overweight according to body fat values estimated by DEXA
Keywords: Adolescent health; Body composition; Obesity; Overweight; Sensitivity and specificity